Molecular mechanisms involved in fruit cracking: A review - Santos, Marlene; Egea-Cortines, Marcos; Gonçalves, Berta; Matos, Manuela (Frontiers in Plant Science, 2023)
Several fleshy fruits are highly affected by cracking, a severe physiological disorder that compromises their quality and causes high economical losses to the producers. Cracking can occur due to physiological, genetic or environmental factors and may happen during fruit growth, development and ripening. Moreover, in fleshy fruits, exocarp plays an important role, acting as a mechanical protective barrier, defending against biotic or abiotic factors. Thus, when biochemical properties of the cuticle + epidermis + hypodermis are affected, cracks appear in the fruit skin. The identification of genes involved in development such as cell wall modifications, biosynthesis and transport of cuticular waxes, cuticular membrane deposition and associated transcription factors provides new insights to better understand how fruit cracking is affected by genetic factors. Amongst the major environmental stresses causing cracking are excessive water during fruit development, leading to imbalances in cations such as Ca. This review focus on expression of key genes in these pathways, in their influence in affected fruits and the potential for molecular breeding programs, aiming to develop cultivars more resistant to cracking under adverse environmental conditions.